Application of molten carbonate fuel cell for CO2 capture in thermal in situ oil sands facilities. (October 2015) - Hill, Richard; Scott, Stephen; Butler, David; Sit, Song P.; Burt, Dan; Narayanan, Raman; Cole, Todd; Li, Christine; Lightbown, Vicki; John Zhou, Z.
Highlights: Incremental cost for steam in the MCFC capture case is about 4% over the base case. The capture cost of MCFC would be about 30% of that for amine-based process. A 76 MW sized MCFC would capture 90% of CO2 from an OTSG for 33 kbod facility. Of the 76 MW generated by the MCFC, approximately 48 MW can be exported. Power export credits may lead to a negative carbon footprint in bitumen production. Abstract: The application of molten carbonate fuel cell (MCFC) technology for carbon capture at a thermal in situ oil sands facility has been studied. A steam assisted gravity drainage (SAGD) facility with once-through steam generator (OTSG) was used as a base case. Engineering modelling was conducted to compare the base case with no carbon capture, and with carbon capture from an OTSG facility using MCFC or amine-based carbon capture. The results indicate that MCFC has the potential to significantly reduce the carbon capture cost at a SAGD facility and to export low GHG intensity electric power. For a 33, 000 barrels of oil per day (or 99, 000 barrels of steam per day) production facility, a 76 MW sized MCFC would be required to capture 90% of CO2 from the OTSG. Of the 76 MW power from MCFC, approximately 48 MW can be exported. If reliably produced, excess power generation may provide CO2 credits by offsetting Alberta grid electricity, possibly leading to a negative carbon footprint in bitumen production. Excess power would also provide a revenue stream to cover some of the cost of capture. The carbon capture cost of MCFC would be about 30% of that for amine-based chemical solvent process.